FOCUS GROUP DISCUSSION TENTANG PENCEGAHAN RISIKO BUNUH DIRI TERHADAP PERILAKU RISIKO BUNUH DIRI PADA REMAJA BERISIKO - Miftakhul Ulfa (Media Husada Journal Of Nursing Science, 2020)
Backgorund: One of the problems in teenagers is suicide. Suicide is one of the impacts of psychiatric disorder that is the current global spotlight. One of the prevention of suicide risks in teenagers can be done by a focus group discussion (fgd). Objective: Analyze the influence of fgd on suicide risk prevention against suicide risk behaviors in adolescents at risk. Research methods: This research used experimental quasi pretest-posttest with control group design with 15 students for the control group and 15 students for the intervention group. Which taken using total sampling technique. Instruments to assess suicide risk behaviors used Beck Suicidal Intent Scale. Scores for suicide behaviours before and after given a fgd were analysed with Wilcoxon statistical trials.Result: Wilcoxon test analysis results obtained P = 0.55 which means p > 0.05. 15 it means that there is no influence offgd on the prevention of suicide risk against suicide risk behavior in adolescents at riskConclusion: There was no influence offgd on the prevention of suicide risk against suicide risk behavior in adolescents at the risk of 1 Bululawang High School.Tip: Further researchers are expected to add longer research time in subsequent studies to explore information on the risk of suicide.